1993
DOI: 10.1152/jappl.1993.75.4.1807
|View full text |Cite
|
Sign up to set email alerts
|

Persistent peripheral vasodilation and sympathetic activity in hypotension after maximal exercise

Abstract: Hemodynamics (by aortic Doppler), autonomic factors (power spectrum analysis of heart rate and blood pressure variabilities and baroreceptor sensitivity), and plasma renin activity during the hypotension after maximal exercise were studied in 10 normal subjects on two separate days: a nonexercise (control) day (30 min of upright rest followed by 60 min of supine rest) and an exercise day (maximal upright bicycle exercise followed by 60 min supine) in random order. After exercise, diastolic pressure was reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
123
0
18

Year Published

1996
1996
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(161 citation statements)
references
References 0 publications
20
123
0
18
Order By: Relevance
“…In both normotensive 33,63 and borderline hypertensive 38,39 individuals, these indirect indices suggest that sympathetic outflow is increased over the same interval in which PEH is observed. This may be a reflexive response to partially offset the exercise induced hypotension.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 87%
See 4 more Smart Citations
“…In both normotensive 33,63 and borderline hypertensive 38,39 individuals, these indirect indices suggest that sympathetic outflow is increased over the same interval in which PEH is observed. This may be a reflexive response to partially offset the exercise induced hypotension.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 87%
“…In those studies that have observed a decline in blood pressure following exercise, the average decrement in pressure was approximately 8/9 (SBP/DBP) mm Hg in the normotensive population, 16,[20][21][22][23]25,[31][32][33][34][35] 14/9 mm Hg in the borderline hypertensive population [10][11][12]34,[36][37][38][39] and 10/7 mm Hg in the hypertensive population. 13 37 We recently examined the effects of the exercising muscle mass by comparing the PEH response to both leg and arm ergometry at the same relative intensity.…”
Section: Magnitude Of the Blood Pressure Declinementioning
confidence: 99%
See 3 more Smart Citations